Cunoj /Khétáne roma műsor, Zalaegerszeg TV
Interview with deputy head of the Roma Department of the Office of National and Ethnic Minorities, Roma minority councils, youth policy, camp for Roma children, emigration of Roma families, suing Hungary at Strasbourg court, discrimination, interest representation, wood carver, first job seekers, evictions, temporary home, leadership training for Roma, Zalaegerszeg